2005
DOI: 10.1007/s10499-005-9002-5
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria associated with early life stages of the great scallop, Pecten maximus: impact on larval survival

Abstract: International audienceA bacteriological study was carried out at a scallop (Pecten maximus) hatchery near Bergen, western Norway following a severe increase in mortality rates during the larval stages of the scallops. No larvae survived to settling, except for those in groups treated prophylactically with chloramphenicol. In order to identify pathogenic strains of bacteria, we performed a challenge test on 10- to 16-day-old larvae using isolated bacterial strains from the hatchery. Infection with six of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 45 publications
4
28
0
1
Order By: Relevance
“…Paillard (2004) has pointed out that infection of bivalve may imply colonization, multiplication, invasion or persistence of the bacteria on or within the host. To Pecten maximus, V. pectenicida was identified as being responsible for mortality outbreaks in hatcheries in France and reported to be present in the stomach, velum fold (Lambert et al, 1998) and gut epithelium of the infected individuals (Torkildsen et al, 2005). In this study, more MM5 were observed in hepatopancreas, which is consistent with the result of TEM, suggesting that hepatopancreas was the susceptible tissue comparing to other tissues.…”
Section: Discussionsupporting
confidence: 86%
“…Paillard (2004) has pointed out that infection of bivalve may imply colonization, multiplication, invasion or persistence of the bacteria on or within the host. To Pecten maximus, V. pectenicida was identified as being responsible for mortality outbreaks in hatcheries in France and reported to be present in the stomach, velum fold (Lambert et al, 1998) and gut epithelium of the infected individuals (Torkildsen et al, 2005). In this study, more MM5 were observed in hepatopancreas, which is consistent with the result of TEM, suggesting that hepatopancreas was the susceptible tissue comparing to other tissues.…”
Section: Discussionsupporting
confidence: 86%
“…In recent years, V. parahaemolyticus has been recognized as a pathogen of scallop P. maximus (Torkildsen et al, 2005), abalone Haliotis diversicolor supertexta (Cai et al, 2006) and shrimp Penaeus monodon Fabricius (Ruangpan and Kitao, 1991). As mentioned above, the sea water temperature at the time when the mortality of clam, M. meretrix happened in Jiangsu Province of China was suitable for the growth and proliferation of V. parahaemolyticus (Kaneko and Colwell, 1973).…”
Section: Discussionmentioning
confidence: 98%
“…These results illustrated the progressive action of the antibiotic on the bacterial community. The improvement of larval survival following chloramphenicol treatment has been previously measured in bivalve hatcheries (Nicolas et al 1996;Gomez-Leon et al 2005;Torkildsen et al 2005). It was suggested in these previous researches that protective effect was probably due to capacity of chloramphenicol to decrease the bacterial load in larval tanks, limiting the proliferation of opportunistic pathogens and thus avoiding the occurrence of massive mortality; However, the use of antibiotic favour the selection of resistant bacteria which represent some risks for health and environment.…”
Section: Characterization Of the Massive Mortalitymentioning
confidence: 99%